PENGARUH LAYANAN MOBILE BANKING DAN RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH PADA PT. BANK NEGARA INDONESIA (PERSERO) Tbk, PEKANBARU - Meliansari Tiya; Nursanti Aida; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research is driven by the acknowledgment of banking ecosystem development inIndonesia, especially in Pekanbaru, which amplifies the competition between the localbanks. Every player gives everything on the table, so which leads the customer toconfusion and disloyalness. This study concentrated on finding the relationship betweenthe quality of Mobile Banking products with customer satisfaction and loyalty by usingRelationship Marketing as an intermediary variable. The insight is gathered from 112BNI Pekanbaru customers using the purposive sampling method. Data that has beencaptured is being analyzed using the Path Analysis method by using the 25th version ofSPSS software. The result shows that the quality of Mobile Banking products somehowinfluences customer satisfaction and loyalty. Furthermore, by using the Path Analysis,Relationship Marketing also can be a go-between the quality of Mobile Banking productsand customer loyalty. Keywords: Mobile Banking Services, Relationship Marketing, Customer Loyalty,Customer Satisfaction